Magnetic behavior of ordered DO3-type Fe3Al Heusler alloy. (2022) - Naveen Kumar, R.; Koppolu, Uma Mahendra Kumar; Rajasabai, Senthur Pandi
Abstract: Fe3 Al alloy is synthesized in a vacuum arc-melting furnace under an argon atmosphere. The prepared ingot is annealed in a vacuum furnace at 800 °C for 1hr, further at 500 °C for 48 hrs to facilitate the re-crystallization. The alloys are crystallized in a cubic DO3 structure. The magnetic properties are derived from M−H, and M−T measurements and the thermal properties like transition temperature (Tc ), heat flow, and heat capacity (Cp ) are measured from DSC. We have observed the magnetic transition at a temperature of 925°K with an applied magnetic field of 5000 Oe. The saturation magnetization (Ms ) is found to be 188 emu/g, and remanence magnetization (Mr ) of 0.78 emu/g. From M−T and DSC measurements it appears that the samples have ferromagnetic ordering with second-order phase transition. The critical exponent is derived by applying mean-field, 3D-Heisenberg, 3D-Ising, and tricritical models.